Corneal neovascularization inhibition and wound healing impregnability of conbercept on rabbit cornea after penetrating keratoplasty. (2nd January 2022) - An, Jianbin; Zeng, Yue; Liu, Huan; Huang, Liying; Yao, Jia; Hou, Enchong; Zhang, Xiaorong
Abstract: Purpose: The inhibitory effect of conbercept on corneal neovascularization (CNV) after penetrating keratoplasty (PKP) and its effect on postoperative wound healing and corneal strength recovery was investigated. Methods: New Zealand white rabbits were randomly divided into 3 groups, two experimental arms A and B and one control arm C. Topical conbercept and subconjunctival injection were carried out respectively after PKP. Slit lamp microscope was used to observe the growth of CNV. The expression of vascular endothelial growth factor (VEGF), placental growth factor (PlGF) and vimentin (Vim) were determined via real-time quantitative polymerase chain reaction (RT-qPCR). The placenta growth factor and vimentin, determination of corneal biomechanical machine strength changed. To measure the maximal strength of the corneal, uniaxial tensile test was carried out on the electroforce 3220-AT biomechanics machine. Results: Two weeks after PKP, CNV appeared, inflammatory cell infiltration and new blood vessel formation were observed in the corneal stroma and superficial stroma layer. Compared with the control arm, the expression levels of VEGF and PlGF in the experimental arms were significantly decreased after using conbercept ( P  < 0.05), and the expression levels reached the maximum at the 4 th week and then decreased gradually. The expression level of Vimentin and corneal intensity increased gradually over time. Conclusion: Conbercept effectively inhibited the formation of CNV after PKP in rabbits, and did not affect postoperative wound healing, nor did it affect postoperative corneal strength recovery.